Actinobacteria and Myxobacteria: Important Resources for Novel Antibiotics (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Bacterial infections cause millions of deaths globally, particularly in children and the elderly, and four of the 10 leading causes of death are infectious diseases in low- and middle-income countries. The continuous use of antibiotics has resulted in multi-resistant bacterial strains all over the world, such as Community-associated Methicillin-resistant Staphylococcus aureus (MRSA), extended-spectrum β-lactamases (ESBLs), and, as expected, hospitals have become breeding grounds for human-associated microorganisms, especially in critical care units.